Reducing the harm from adolescent alcohol consumption: Results from an adapted version of SHAHRP in Northern Ireland - McKay, M.; McBride, Nyanda; Sumnall, H.; Cole, J. (Informa Healthcare, 2012)
Background: The study aimed to trial an adapted version of the School Health and Alcohol Harm Reduction Project (SHAHRP) in Northern Ireland. The intervention aims to enhance alcohol related knowledge, create more healthy alcohol-related attitudes and reduce alcohol-related harms in 14–16-year-olds. Method: A non-randomised control longitudinal design with intervention and control groups assessed students at baseline and 12, 24 and 32 months after baseline. Students were from post-primary schools (high schools) in the Eastern Health Board Area in Northern Ireland. Two thousand three hundred and forty nine participants were recruited at baseline (mean age 13.84) with an attrition rate of 12.8% at 32-month follow-up. The intervention was an adapted, culturally competent version of SHAHRP, a curriculum programme delivered in two consecutive academic years, with an explicit harm reduction goal. Knowledge, attitudes, alcohol consumption, context of use, harm associated with own alcohol use and the alcohol use of other people were assessed at all time points. Results: There were significant intervention effects on all measures (intervention vs. controls) with differential effects observed for teacher-delivered and outside facilitator-delivered SHAHRP. Conclusion: The study provides evidence of the cultural applicability of a harm reduction intervention (SHAHRP) for risky drinking in adolescents in a UK context.